Bom Waktu Penyelenggaraan Sistem PEnsiun PNS di Indonesia - Tri, Agustinus Sulistyo (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
Implementation of civil servant pension system in Indonesia is like a time bomb that could explode at any time. There are five fundamental problems identified in the implementation of civil servant pension system. The problems are the financing of the pension plan, pension fund management, pension fund management institutions, pension participants and pension benefits. The solutions of these problems must be precise and comprehensive. In an effort to reform civil servant pensions system, there are three components that must be updated, (1) the participant, (2) pension program which includes a pension program funding, investment funds, and pension benefits, and (3) institutions with authority to administer the pension plan.